Class and its others - Gibson-Graham, J. K.; Resnick, Stephen A.; Wolff, Richard D. (University of Minnesota Press, 2000)
Offers new and compelling ways to look at class through examinations of such topics as sex work, the experiences of African American women as domestic laborers, and blue- and white-collar workers. This work acknowledges that individuals may participate in various class relations at one moment or over time and that class identities are multiple and changing. Taken together, the essays in this book will prompt a rethinking of class and class subjectivity that will expand social theory.